Lipid-Mediated Oxidative Stress and Inflammation in the Pathogenesis of Parkinson's Disease - Tahira Farooqui; Akhlaq A. Farooqui (Parkinson's Disease)
Parkinson's disease (PD) is a neurodegenerative movement disorder of unknown etiology. PD is characterized by the progressive loss of dopaminergic neurons in the substantia nigra, depletion of dopamine in the striatum, abnormal mitochondrial and proteasomal functions, and accumulation of α-synuclein that may be closely associated with pathological and clinical abnormalities. Increasing evidence indicates that both oxidative stress and inflammation may play a fundamental role in the pathogenesis of PD. Oxidative stress is characterized by increase in reactive oxygen species (ROS) and depletion of glutathione. Lipid mediators for oxidative stress include 4-hydroxynonenal, isoprostanes, isofurans, isoketals, neuroprostanes, and neurofurans. Neuroinflammation is characterized by activated microglial cells that generate proinflammatory cytokines, such as TNF-α and IL-1β. Proinflammatory lipid mediators include prostaglandins and platelet activating factor, together with cytokines may play a prominent role in mediating the progressive neurodegeneration in PD.